INSTITUTIONALIZATION, CORPORATE REPUTATION AND CUSTOMER SATISFACTION RELATIONSHIP: AN APPLICATION IN LOCAL GOVERNMENT (Third Sector Social Economic Review, 2024)
The purpose of this research is to determine the relationship between institutionalization level, corporate reputation perception, and satisfaction, and to uncover potential effects. In line with the research objective, data were collected through surveys from 426 employees working in 6 central metropolitan district municipalities of Ankara province, as well as from 426 citizens receiving services from these municipalities. Correlation analysis was conducted to test the main hypotheses developed to identify the relationship between institutionalization level, corporate reputation perception, and citizen satisfaction, while regression analysis was employed to determine the impact levels for the sub-hypotheses developed. According to the findings obtained from the analyses, a strong positive relationship was identified between institutionalization level and corporate reputation, indicating a significant effect of institutionalization on corporate reputation. However, no significant relationship was found between institutionalization and corporate reputation levels with citizen satisfaction levels. It is believed that these results will provide researchers with a different perspective on institutionalization, corporate reputation, and satisfaction compared to widely held views, and contribute to a better understanding of the current institutional structure of municipalities. In order to increase the level of institutionalization, corporate reputation and satisfaction in local governments, appointments to be made should be based on merit in a way that does not harm the functioning of the institution. It is also recommended that regular feedback should be received from both employees and citizens and activities should be carried out accordingly.
Keywords: Instituonalization; Corporate Reputation; Satisfaction; Local Government; Municipality; Citizen